Primary Care Physicians' Perceived Barriers to Optimal Dementia Care: A Systematic Review. (25th June 2018) - Mansfield, Elise; Noble, Natasha; Sanson-Fisher, Rob; Mazza, Danielle; Bryant, Jamie
Abstract: Background and Objectives: Primary care physicians (PCPs) have a key role in providing care for people with dementia and their carers, however, a range of barriers prevent them from delivering optimal care. We reviewed studies on PCPs' perceptions of barriers to providing optimal dementia care, including their methodological quality, whether they focused on barriers related to diagnosis and/or management, and the patient-, provider-, and system-level barriers identified. Research Design and Methods: Studies were included if they were quantitative studies published since 2006 which reported on PCPs' perceptions of the barriers to providing dementia care. The methodological quality of identified studies was assessed using an adapted version of accepted rating criteria for quantitative studies. Data were extracted from studies which were rated as "moderate" or "strong" quality. Results: A total of 20 studies were identified, 16 of which were rated as "moderate" or "strong" methodological quality. Patient-related barriers included a reluctance to acknowledge cognitive decline and patient nonadherence to management plans. Provider-related barriers included a lack of training and confidence. System-related barriers included a lack of time during consultations and lack of support services. Discussion and Implications: This review highlights a range of barriers to dementia diagnosis and management from studies rated as being methodologically adequate. Future studies should also utilize theory-driven approaches to exploring a comprehensive range of barriers to optimal dementia care across the care trajectory.